General and healthcare-related HIV stigma among cisgender Brazilian women: the role of socioeconomic vulnerability - Angelo Brandelli Costa; Murilo Martins da Silva; Lara Wiehe Chaves; Milena Gelain; Isadora Graeff Bins-Ely; Felipe Alckmin-Carvalho; Guilherme Welter Wendt (HIV Research & Clinical Practice)
Background HIV-related stigma is associated with worse health outcomes and lower adherence to antiretroviral therapy. There is limited data on the stigma faced by Latin American cisgender women, although they are among the populations most affected by HIV. This study aims to provide insight into the Stigma Index Brazil, with the objective of estimating the prevalence of HIV-related stigma among cisgender women in Brazil and to investigate the role of low socioeconomic status in stigma experience. Methods This is a cross-sectional community-based study. A total of 30 people with HIV were trained to recruit participants from their peer networks; 1,768 people with HIV from all regions of Brazil participated in the study, of which 566 participants were cisgender women. We used the Stigma Index, an instrument that assesses global trends in HIV-related stigma from the perspective of people with HIV. Results Approximately 70% of participants reported some form of HIV-related stigma. The most prevalent forms were discriminatory comments or gossiping (51.26%) and verbal harassment (30.99%). More than 20% experienced any health care related HIV-stigma in the last 12 months, the most frequent being the avoidance of physical contact (10.02%). Women in social vulnerability faced more stigma compared to the group without social vulnerability, both in general contexts (75.79% vs 64.32%; χ2 = 8.67, p < 0.05) and in healthcare contexts (24.12% vs 16.02%; χ2 = 4.06, p < 0.05). Conclusion We found a high prevalence of stigma associated with HIV faced by Brazilian women from all regions of the country, both in everyday life and in healthcare contexts. Evidence-based interventions to reduce stigma in the general population, and specific mental health care aimed at women with HIV in Brazil, especially among those with greater socioeconomic vulnerability, are urgent.